A Chitosan/Urushi Anion Exchange Membrane for a Nonaqueous Redox Flow Battery - Gong, Sung-Jun; Kim, Dongyoung; Cho, Eunhae; Hwang, Seung Sang; Won, Jongok (WILEY-V C H VERLAG GMBH, 2017)
A new bio-based anion exchange composite membrane that consists of a chitosan/urushi (C/U) pseudo-interpenetrating polymer network (IPN) coated on the surface of a porous support was prepared for non-aqueous redox flow battery (RFB). Celgard membranes composed of polypropylene were used as the porous support. A C/U pseudo-IPN film was formed by laccase-catalysed polymerization and aerobic oxidative polymerization. The ion conductivity increased with an increasing amount of chitosan in the C/U coating layer, and the composite membranes had lower vanadium acetylacetonate permeability than a pristine Celgard support. The performance of a non-aqueous RFB increased with an increasing amount of chitosan in the C/U layer in the surface-modified Celgard membrane. The coulombic efficiency and energy efficiency values were 66% and 40.5%, respectively, for a RFB with a surface-modified membrane that contained 17 wt% chitosan in the C/U layer. These values were higher than those of the commercial Neosepta AHA membrane, which had a dense structure, indicating that the C/U pseudo-IPN layer on the porous support provided the selectivity of the redox active species.
Keywords: POLYIMIDE/CHITOSAN COMPOSITE MEMBRANE; PERFORMANCE; POLYMERIZATION; SEPARATORS; CROSSOVER; CELL